A Eficácia do Uso de uma Abordagem Via Gêneros Textuais no Ensino da Habilidade de Produção Escrita em Inglês como Língua Estrangeira, para Alunos do Ensino Fundamental: um Estudo de Caso - Maria Raquel de Andrade Bambirra (2004)
This research study investigated the use of a textual genre approach to the teaching of writing in English as a second language, to students of Ensino Fundamental, in Brazil. Its theoretical support is in Halliday's context of culture, specifically in field, tenor and mode categories, as well as in Hasan's context of situation, so as to elicit the generic structure of texts through their obligatory, optional, and recursive elements. Two groups at 8ª serie do Ensino Fundamental, at a traditional school in Belo Horizonte, together with their regular English teacher, were the subjects of this study at its empirical part, during seven months. An approach to writing as a process, via textual genrees, was adopted to one of the groups. In the other group, the approach to writing as a product, as established by the school pedagogical project, was maintained. In order to check the impact of this approach via textual genres in the students written produciton, the students were asked to write seven compositions. Also, both students and teacher answered two questionnaires, at the beginning and end of research respectively. The collected dada point to the conclusion that the approach to the teaching of writing as a process, via textual genres, besides motivating the students, was also relevant to improve the way they realize texts and their writing itsefl as a consequence. In addition, it has proved to be very helpful in organizing the students' thinking and also enhancing their ability in creating texts good enough to meet their social function more efficiently, considering the communicative context in which they are inserted.